Identification of Klebsiella pneumoniae in microwavable chicken curries using 16s rRNA analysis - Wong, C. Y.; Rao, P. V.; Soon, J. M. (2018)
Microwave heating technology is widely used in food catering and domestic households. Nonuniformity of microwave temperature distribution causes the formation of hot and cold spots in heated product has led to the survival of foodborne pathogens which may later cause food borne diseases. It is the aim of this study to determine the effect of different microwave heating on the microbiological quality of microwavable frozen chicken curries. Nine commercialised frozen chicken curries were thawed overnight in the chiller (< 4°C) and exposed to different microwave power levels and times (270 W at 60 s; 950 W at 150 s and 300 s). 25 g of chicken curry were homogenised, serial diluted and enumerated aseptically. Total Aerobic Count (TAC), Total Coliform Count (TCC), Escherichia coli count and Salmonella count were carried out and no microorganisms were detected. Enterobacteriaceae were found in the food samples after enrichment process. Polymerase Chain Reaction (PCR) amplification and 16S ribosomal ribonucleic acid (rRNA) sequencing were carried out. Results of 16S rRNA sequence analysis indicated that two gram-negative isolates after enrichment were identified as Klebsiella pneumoniae.